The Role and Strategy of Extension in the Indonesian Marine and Fisheries Sector - Angkasa Putra; Sarifah Aini (Social Science Studies, 2023)
Counseling as a two-way active process between the instructor and the extension worker aims to build a behavior change process. Extension officers disseminate information and provide information to the public. The process adopted adheres to the principles of being consistent and continuous, with maximum effort and thought, time-consuming and tiring, until in the end the beneficiaries of the counseling experience a change for the better. The purpose of this study is to analyze the role and strategy of extension in the marine and fisheries sector in Indonesia. Based on the studies conducted, extension officers in the marine and fisheries sector have a strategic role in determining the success of marine and fisheries development in the field. Outreach strategy for the marine and fisheries sector through structuring and increasing institutional capacity.